2018
DOI: 10.1111/dme.13787
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of a body shape index and body roundness index to identify diabetes mellitus in Han Chinese people in Northeast China: a cross‐sectional study

Abstract: BMI, a body shape index and body roundness index may identify the presence of diabetes. Among the three anthropometric indices, BMI had the weakest association with diabetes. Body roundness index is an alternative index for assessing diabetes in Han Chinese people in Northeast China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 21 publications
(50 reference statements)
3
62
0
1
Order By: Relevance
“…It appeara that BRI has become a competitive surrogate for diabetes prediction because of its historically consistently good performance. In two cross‐sectional studies and one prospective study with a five‐year follow‐up, BRI was positively associated with incident diabetes risk . Interestingly, participants from those three studies were all of a Chinese background.…”
Section: Discussionmentioning
confidence: 98%
“…It appeara that BRI has become a competitive surrogate for diabetes prediction because of its historically consistently good performance. In two cross‐sectional studies and one prospective study with a five‐year follow‐up, BRI was positively associated with incident diabetes risk . Interestingly, participants from those three studies were all of a Chinese background.…”
Section: Discussionmentioning
confidence: 98%
“…However, BRI is limited in predicting percentage of fat mass in elite athletes when compared with other commonly and readily available field methods such as bio‐impedance analysis or skinfold prediction models 63 . Several recent studies have shown that BRI could be used as an adipose indicator for determining the presence of eccentric left ventricular hypertrophy, 64 hyperuricaemia, 41,65 arterial stiffness, 66–69 CVD, 70,71 diabetes, 41,72–75 dyslipidaemia, 41,76–78 hypertension 41,79,80 and MetS 41–55 …”
Section: Discussionmentioning
confidence: 99%
“…A body shape index (ABSI), using a standardized WC based on BMI and height, reflects mortality hazard better than BMI and WC [15]. While, the body roundness index (BRI), is an indicator of body fat and visceral adipose tissue percentage, and may be useful for evaluating health status [15].…”
Section: Introductionmentioning
confidence: 99%